Evaluation of the cytotoxicity of Alpinia officinarum rhizome extract against some cancer cells in vitro - Al-Shabani, Baneen Muhsin Oudah; Al-Shaikh, Sharaf Ali Hadi (International Journal of Aquatic Research and Environmental Studies, 2026)
The current study aimed to evaluate the cytotoxicity of aqueous and alcoholic extracts of galangal rhizome against certain cancer cells and to select the optimal cell line exhibiting the highest inhibition rate, the chemical content and total phenolic and flavonoid content were estimated, and antioxidant levels were measured using DPPH assay, the cytotoxicity of the galangal extracts was then investigated using the MTT assay to determine their toxicity and ability to inhibit the growth of specific cancer cells, namely HepG2 liver cancer cells, Coco-2 colon cancer cells, and MCF-7 breast cancer cells, and compared to normal WRL68 cells in vitro. The results showed a variation in the chemical content of galangal rhizome, and also showed a significant difference in the amount of flavonoids and phenols between the extracts. Compounds effective against microorganisms and cancer were obtained using GC-Mass, and there were significant differences in antioxidants at concentrations of 0.12 and 0.25 mg/ml, and no significant differences at concentrations of 0.5 and 1 mg/ml between the aqueous and alcoholic extracts. The results also showed that the aqueous and alcoholic extract of galangal rhizome effectively inhibits the growth of cancer cells at a concentration of 400 µg/mL, with inhibition rates of (68.29, 58.72, 35.61) % for the cell types respectively. The HepG2 liver cancer cell line was selected based on the MTT results, as it had the highest inhibition rate for the cancer cells under study. Cytotoxicity was then assessed by performing the HCS detection assay to measure the cellular indicators represented by Viable Cell Count (VCC), Total Nuclear Intensity (TNI), Cell Membrane Permeability (CMP), Mitochondrial Membrane Potential (MMP), and Cytochrome C releasing (CC). The results indicated a decrease in the number of viable cell carcinomas (VCCs) of HepG2 liver cells, particularly at concentrations of 100 and 200 µg/mL, by 34.48% and 38.22%, respectively. There was also a significant increase in (TNI) at a significance level of p < 0.05, by 26.85% and 66.88%, respectively. A clear effect on (MMP) was also observed, by 26.45% and 31.03%, respectively. Furthermore, there was a significant increase in cytochrome C (CC) release levels, by 47.67% and 62.63%, respectively. These findings suggest that the galangal rhizome extract possesses high inhibitory activity against the cancer cells under study in vitro.
Keywords: Antioxidant; phenols; Flavonoids; Cell line cancer; liver cancer HepG2